Gender dysphoria and attention problems: possible clue for biological underpinnings - ERDOĞDU, AYŞE BURCU; PERDAHLI FİŞ, NEŞE (TAYLOR & FRANCIS LTD, 2017)
OBJECTIVES: Development of gender identity is a complicated process. Several biological, familial, environmental, and cognitive factors thought to play role during this process. When a person has a persistent discomfort with his/her assigned gender and exhibits cross-gender identification, gender dysphoria is to be considered. In this study, we aimed to determine the rates of psychiatric diagnoses in youth presenting with gender dysphoria and compare them with a control group in terms of family functioning, emotional, and behavioural problems. METHODS: The study sample consisted of 20 cases with gender dysphoria and 40 controls (5-17 years of age). The instruments included were Sociodemographic Form, Family Assessment Device (FAD), Child Behavior Checklist, and Schedule for Affective Disorders and Schizophrenia for School Aged Children Present-Lifetime Version. RESULTS: Ninety per cent of the cases with gender dysphoria had at least one psychiatric diagnosis. Attention-deficit/hyperactivity disorder (ADHD) (75%) was the leading comorbidity, followed by major depressive disorder (25%). Gender dysphoria group had significantly higher scores in communication, roles, affective involvement, and general family functioning subscales of FAD and in all Child Behavior Checklist subscales. High Child Behavior Checklist attention subscale score was significantly associated with the diagnosis of gender dysphoria in binary logistic regression analysis (odds ratio: 0.82; p < .001). CONCLUSIONS: Our results pointed out a possible biological background for gender dysphoria, along with psychosocial/psychodynamic explanations. The individuals with gender dysphoria will benefit from an integrative approach where all possible contributing factors are considered. Therefore, in addition to psychosocial and psychodynamic evaluation, assessment and interventions regarding ADHD will help to improve well-being and quality of life of these individuals.
Keywords: Gender dysphoria; youth; attention problems; AUTISM SPECTRUM DISORDERS; IDENTITY-DISORDER; PSYCHIATRIC COMORBIDITY; CHILDREN; ADOLESCENTS; YOUTH; BOYS